Sistem Informasi Pengaduan Masyarakat Berbasis Web Pada Kelurahan Besusu Timur Palu - Masse, Fitriyanti A.; Grace, Diana; Burhanuddin , Burhanuddin (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
The rapid development of information and communication technology has had a significant impact on various aspects of life. This development had an impact especially in terms of public complaints. Researchers want to develop a public complaint system for the continuous improvement of public facilities and infrastructure in the East Besusu sub-district environment and to find out the situation and conditions that occur in the East Besusu sub-district. The system was developed using the Waterfall model, the design uses UML and MySQL database. The result of the research is a web-based information system that facilitates the community in reporting and complaints about public facilities and infrastructure in the East Besusu sub-district.